Community Empowerment Strategies to Combat Poverty (Case Study at UPTD Vocational Training Center in Tebing Tinggi City) - Arjun, Devi; Batubara, Chuzaimah; Nasution, Yenni Samri J. (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This research aims to discover the main priority strategies for community empowerment to combat poverty by presenting the internal and external conditions that have been implemented so far. Then, as an addition, the researcher also presents several urgent measures that need to be implemented so that community empowerment can be more focused. The method used is a qualitative method employing SWOT and QSPM analysis. The number of respondents who filled out the questionnaire consists of 5 respondents from the community who participated in training at the UPTD Tebing Tinggi Vocational Training Center and 5 respondents from expert specialists. Based on the results of the SWOT analysis, the strategy quadrant obtained after being processed in the IFE and EFE matrices is in Quadrant I. This indicates that the strategy used is a progressive strategy. This strategy means that the company has strengths and opportunities. Next, in the QSPM analysis, the result shows that the main priority strategy that must be implemented is to enhance training programs to increase job opportunities for participants.